2022
DOI: 10.3390/insects13050444
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Isolates Derived from Nest Soil Affect the Attraction and Digging Behavior of Workers of the Red Imported Fire Ant, Solenopsis invicta Buren

Abstract: Populations of monogyne and polygyne red imported fire ants (RIFA), Solenopsis invicta Buren, are distributed throughout the southern United States. This ant species is hazardous to farm animals and workers, damages infrastructure, and depletes native arthropod populations. Colony expansion is affected by several biotic factors, but the effects of soil microbes on ant behavior related to soil excavation within nest sites have not been investigated. Consequently, we cultured bacteria from RIFA nest soils. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…and “avoided” strains ( Arthrobacter sp., Microbacterium sp., and E. cloacae ) may have potential attraction or avoidance effects on female L. invasa . Several previous studies unveiled different bacterial species’ attraction or avoidance effects and their metabolites on a broad spectrum of insect behaviors [ 42 ]. In the case of Solenopsis invicta , it was observed that the Arthrobacter woluwensis cultured in its nest soil can attract worker ants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and “avoided” strains ( Arthrobacter sp., Microbacterium sp., and E. cloacae ) may have potential attraction or avoidance effects on female L. invasa . Several previous studies unveiled different bacterial species’ attraction or avoidance effects and their metabolites on a broad spectrum of insect behaviors [ 42 ]. In the case of Solenopsis invicta , it was observed that the Arthrobacter woluwensis cultured in its nest soil can attract worker ants.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Solenopsis invicta , it was observed that the Arthrobacter woluwensis cultured in its nest soil can attract worker ants. In contrast, several Firmicutes bacteria, including Bacillus , Paenibacillus , Brevibacillus , and other species, typically exhibited an avoidance effect on ants [ 42 ]. Further studies have shown that K. oxytoca and Citrobacter freundii significantly lured female stable flies [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since RIFAs secrete venom alkaloids on the interior surfaces of their nests to disinfect their habitat and larval surfaces [ 8 ], the amount of venom alkaloids secreted can affect the amount of bacteria in the soil to some extent. Newly mated RIFA queens can use scent to locate Actinobacteria-rich soil for nesting [ 40 ], and worker ants also prefer to expand their nests in Actinobacteria-rich soil [ 41 ]. Soil-nesting insects have a symbiotic relationship with Actinobacteria; this can produce antibiotics to protect insects from pathogenic bacteria and fungi [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…People who are allergic to red imported fire ants may experience burning pain, followed by redness, swelling, itching, high fever, and, in severe cases, shock or even death [9]. Red imported fire ants also congregate around uninsulated electrical equipment, causing short circuits and interfering with regular switch operation, damaging agricultural machinery and equipment, and interfering with manual operation [10,11]. Red imported fire ants cause enormous economic harm, costing the United States more than USD 6 billion per year in damage restoration, medical care, and control measures [12,13].…”
Section: Introductionmentioning
confidence: 99%